Enhancing rice water productivity: insights from crop water needs and irrigation in Pakistan - Akbar, G.; Sadozai, N. L.; Ashraf, Muhammad (Wiley, 2025)
Excessive irrigation significantly reduces rice (Oryza sativa L.) water productivity in Pakistan. This study evaluated crop water requirements, irrigation trends and water productivity across Pakistan's rice-growing regions. Field data on crop yield, soil characteristics, irrigation practices and 10 years of weather data were collected from 11 districts across four provinces. The FAO AquaCrop model was used to assess crop water requirements (evapotranspiration, ET), the root zone water balance and water productivity. The crop water requirements ranged from 787 to 1151 mm, while irrigation consistently exceeded these needs by 95% to 123%. The irrigation water productivity (WPi) ranged from 0.09 to 0.19 kg/m3, and the evapotranspiration (ET) water productivity (WPet) ranged from 0.20 to 0.41 kg/m3. Excessive irrigation, 2 to 3 times the actual crop water needs, is attributed to traditional practices, a lack of knowledge and suboptimal irrigation schedules. Optimizing irrigation scheduling, adopting advanced technologies, and using high-yielding, drought-tolerant rice varieties could reduce water losses and improve crop yields. These findings offer actionable strategies to increase water productivity and ensure food security in Pakistan's rice-growing regions, with potential applications in other water-scarce, rice-producing countries facing similar challenges.